Lung ventilation and the strength of the respiratory muscles of women in the third trimester of pregnancy in the aspect of physical activity - P. Okrzymowska; M. Kurtys; N. Smolarek; M. Kurzaj; R. Slopien; K. Rozek-Piechura (IMR Press, 2020)
The research concerned assessment of the respiratory function and function of the respiratory muscles of women in the third trimester of pregnancy in terms of the level of their physical activity. Using the ATS/ERS assessment criterion, there was no lung ventilation disorder in the studied groups of women. The results of the study indicate that in women who were more active, the values of all measured functional parameters of the respiratory system were higher. In almost all women, irrespective of the level of physical activity, the strength of the inspiratory muscles was found to decrease. The majority of surveyed women undertook physical activity in the form of walking with varying frequency during the week, but only a few of them had undertaken a more intense physical effort. Pregnant women frequently do not undertake more demanding activities due to concerns about the child.